2020
DOI: 10.2147/cmar.s250632
|View full text |Cite
|
Sign up to set email alerts
|

<p>Current Therapeutic Progress of CDK4/6 Inhibitors in Breast Cancer</p>

Abstract: The clinical use of selective cyclin-dependent kinase (CDK) 4/6 inhibitors has significantly improved the prognosis of patients with hormone receptor (HR)-positive human epidermal growth factor receptor 2 (HER2)-negative advanced or metastatic breast cancer (ABC/mBC), which almost achieved the double progression-free survival (PFS) in combination with endocrine therapy (ET) compared with ET alone. To date, there are 3 CDK4/6 inhibitors (palbociclib, ribocilcib and abemaciclib) approved by the US Food and Drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 92 publications
0
26
0
Order By: Relevance
“…One class of targeted therapeutics that may benefit from the modification of senescence is the CDK4/6 inhibitors (CDK4/6i). Specifically, three CDK4/6i, including Palbociclib, Ribociclib, and Abemaciclib, have been approved for the treatment of patients with hormone receptor-positive and human epidermal growth factor receptor 2-negative breast cancer and are under evaluation in clinical trials for other cancers such as melanoma [13][14][15][16]. Further, the CDK4/6i Palbociclib has been shown to induce senescence in a variety of cancer cell lines that express functional retinoblastoma protein (pRB) as well as in solid tumors in vivo [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…One class of targeted therapeutics that may benefit from the modification of senescence is the CDK4/6 inhibitors (CDK4/6i). Specifically, three CDK4/6i, including Palbociclib, Ribociclib, and Abemaciclib, have been approved for the treatment of patients with hormone receptor-positive and human epidermal growth factor receptor 2-negative breast cancer and are under evaluation in clinical trials for other cancers such as melanoma [13][14][15][16]. Further, the CDK4/6i Palbociclib has been shown to induce senescence in a variety of cancer cell lines that express functional retinoblastoma protein (pRB) as well as in solid tumors in vivo [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…CDKN2C interacts with cyclin-dependent kinases 4 and 6 (CDK4/6) and prevents their activation (115,116). Three CDK4/6 inhibitors have been approved for treatment of hormone receptor+/HER2+ breast cancer: palbociclib, ribociclib and abemaciclib (117,118). Ongoing clinical studies in other types of solid tumors including ESCC have been reported (119).…”
Section: Lncrna Linp1 Induces Epithelial-mesenchymal Transitionmentioning
confidence: 99%
“…The pan‐CDK inhibitor roscovitine is in phase II clinical trial for colitis and cystic fibrosis, both neutrophil‐mediated diseases 13 . CDK4/6 inhibitors, such as palbociclib, ribocilcib, and abemaciclib, are approved to treat metastatic breast cancer 14,15 . Since neutrophils also play a prominent role in the progression of cancer, 16 it is possible that neutrophil suppression contributed to the therapeutic outcome.…”
Section: Introductionmentioning
confidence: 99%